Case-Based Lessons in the Management of Complex Hepato-Pancreato-Biliary Surgery - Pawlik, Timothy M.; Weber, Sharon; Gamblin, T. Clark (Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive, state-of-the art definitive "case-based" reference for the work-up, diagnosis, intraoperative management, and peri-operative care of patients with complex, difficult to manage HPB diseases. The book provides a practical, clinically useful guide that reviews select complicated HPB cases, as well as providing key information on how to manage such patients. This text provides detailed "case-based" algorithms, as well as specific guidance on the management of complicated HPB patients. In addition, it also focuses on key points on how to work-up patients pre-operatively, highlights intra-operative technical "pearls", and defines optimal post-operative care. Chapters are rich with images, have multiple "call out" boxes to highlight key lessons learned and also include clinical management "pearls." All chapters are written by experts in their field and include the most up-to-date clinical information from national and world leaders in their respective discipline. Case-Based Lessons in the Management of Complex Hepato-Pancreato-Biliary Surgery will serve as a very useful resource for physicians, fellows and residents dealing with complex HPB patients. In addition, It will provide a concise yet comprehensive summary of the diagnosis, work-up, and management of some of the most complex, yet common, HPB cases.